Effects of continuous glucose monitoring in enhanced recovery after colorectal cancer patient surgery with type 2 diabetes (application of CGM in the ERAS process of CRC patient with diabetes) - Wang, Qinbo; Zhou, Yuan; Wang, Wanzhen; Ou, Yingjuan; Wu, Xia; Chen, Junrong; Li, Xiaoyan; Li, Hua (Frontiers in Medicine, 2025)
ObjectivesThis study aimed to evaluate the impact of Continuous Glucose Monitoring (CGM) on enhanced recovery after surgery (ERAS) outcomes in colorectal cancer (CRC) patients with type 2 diabetes mellitus (T2DM).MethodsWe conducted an observational cohort study of adult patients (≥18 years) with T2DM undergoing abdominal surgery for pathologically confirmed CRC. Exclusion criteria included history of other malignancies, preoperative infections, or incomplete clinical data. Participants were stratified into two groups: the exposed group (CGM monitoring) and the control group (conventional glucose analyzer [CGA]). Primary outcomes included glycemic variability, surgical complications, ERAS milestones, and patient satisfaction scores.ResultsAmong 181 enrolled patients (CGM = 81, CGA = 100), CGM demonstrated superior glycemic control compared to CGA, with significantly lower mean daily glucose levels at postoperative day 1 (9.52 ± 2.53 vs. 10.37 ± 2.26 mmol/L, p < 0.05) and day 3 (9.36 ± 1.82 vs. 10.64 ± 1.84 mmol/L, p < 0.05). The CGM group showed better clinical outcomes including improved anastomotic healing (p < 0.05), shorter time to first flatus (p < 0.05), and reduced length of hospitalization (p < 0.05). Patient satisfaction scores were significantly higher in the CGM group (32.42 ± 3.33 vs. 29.81 ± 2.98, p < 0.05).ConclusionCGM provides superior perioperative glucose monitoring in diabetic CRC patients, particularly during the critical 72-h postoperative period. The technology facilitates early detection of acute hyperglycemia, promotes wound healing, and accelerates recovery within ERAS protocols. These findings support the clinical value of CGM implementation in surgical management of T2DM patients with CRC.